Electrically detected and conventional magnetic resonance investigation of surface and bulk states in polyaniline thin films - Castro, Fernando A.; Graeff, Carlos Frederico de Oliveira [UNESP] (American Institute of Physics (AIP), 2007)
Electrically detected magnetic resonance (EDMR) and electron paramagnetic resonance (EPR) were used to investigate emeraldine base polyaniline films. The magnetic susceptibility presented a Curie (localized spins)-Pauli (delocalized spins) transition at 240 K, when we also observed a transition in the dependence of the g factor with temperature (T). Peak-to-peak linewidth decreases with increasing temperature, reflecting that motional narrowing limits the hyperfine and dipolar broadening in this polymer. EDMR spectra could only be observed above 250 K in accordance to EPR results. Surface and bulk transport could be separated and their analysis reflected the effect of magnetic interaction with oxygen. (c) 2007 American Institute of Physics.